2009
DOI: 10.1021/ma9019015
|View full text |Cite
|
Sign up to set email alerts
|

Lectin Recognizable Biomaterials Synthesized via Nitroxide-Mediated Polymerization of a Methacryloyl Galactose Monomer

Abstract: The preparation of poly(2-(2′,3′,4′,6′-tetra-O-acetyl-β-d-galactosyloxy)ethyl methacrylate-co-styrene) (P(AcGalEMA-co-S)) glycopolymer was performed via nitroxide-mediated polymerization using a methacrylic acid-based alkoxyamine with N-tert-butyl-N-(1-diethylphosphono-2,2-dimethylpropyl) (SG1) nitroxide as mediating agent. In the presence of a low proportion of styrene, the polymerization of the glycomonomer was conducted in a controlled fashion at 85 °C. The synthesis of the diblock copolymers was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
131
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 85 publications
1
131
0
1
Order By: Relevance
“…(NMP) [29,30], reversible addition-fragmentation chain transfer (RAFT) [31][32][33][34] and cyanoxyl-mediated radical polymerization [35,36]. In the present study, a series of well-defined random copolymers comprising different sugar-based methacrylates and methyl methacrylates were synthesized by ATRP and their structures were investigated by spectroscopic, chromatographic and thermal analyses.…”
mentioning
confidence: 97%
“…(NMP) [29,30], reversible addition-fragmentation chain transfer (RAFT) [31][32][33][34] and cyanoxyl-mediated radical polymerization [35,36]. In the present study, a series of well-defined random copolymers comprising different sugar-based methacrylates and methyl methacrylates were synthesized by ATRP and their structures were investigated by spectroscopic, chromatographic and thermal analyses.…”
mentioning
confidence: 97%
“…Galactosylated porous films on protein patterning could also be used as a screening device. 191 Xiong et al studied the use of linear PS and star-shaped PS-block-polybutadiene copolymer solutions that have been cast in a static humid environment and investigated the influence of the flow ability of polymer solution and water vapor pressure on the final film structure by using different starting polymer concentrations at 4 to 90 • C. They found that higher solvent vapor pressure would be required for the fabrication of ordered patterns having smaller pores and initial polymer concentration has an important effect on the packing of condensed water droplets since the polymer solution could reach a level of 'solidification' during a reasonable time of solvent evaporation that fixes the droplets and prevents the droplets from coalescing. …”
mentioning
confidence: 99%
“…A statistical copolymer of M9 with N,N′-di(octadecyl)acrylamide M8 was also prepared under similar conditions and with similar results (p = 55% after 40 h, Đ = 1.2; Entry 14, Table 1). Amphiphilic lipo-glycopolymers were obtained after Ting et al [86] reported the synthesis of an amphiphilic glycopolymer bearing α-galactoside residues (Entry 11-12, Table 1). Initially, methacrylate glycomonomer M11 was copolymerized with styrene in the presence of N9 as the initiator to afford fairly uniform poly(M11 0.9 -stat-St 0.1 ) (1,4-dioxane, 85 °C, 2.7 h).…”
Section: Synthesis Of Glycopolymers By Stable Free Radical Polymerizamentioning
confidence: 99%